THE IMPORTANCE OF DEVELOPING CRITICAL THINKING SKILLS OF YOUTH - Shukurova, Shokhsanam Kakhramon kizi (Educational Research in Universal Sciences, 2023)
The article highlights the main issues of the development of youth critical thinking skills: the relevance of this problem is substantiated, the essence and signs of critical thinking as a psychological, pedagogical and social category are considered. The principles and didactic foundations for the development of students’ critical thinking are outlined, and the factors that determine the success of this process are identified. The article is aimed at forming a holistic view of critical thinking as one of the conditions for the social success of young people.